EAA Women Soar – Expanding Horizons - Skiles, Jeffrey (Proceedings of the Wisconsin Space Conference, 2012)
Women Soar brings together young women with female mentors who help to expose the participants to math, science, and technology through aviation. Participants have a chance to learn more about programs that can support career goals that have traditionally been male dominated and are able to network with one another to provide support for themselves.Â